2021
DOI: 10.3389/fimmu.2021.615369
|View full text |Cite
|
Sign up to set email alerts
|

Clonorchis sinensis-Derived Protein Attenuates Inflammation and New Bone Formation in Ankylosing Spondylitis

Abstract: Helminth infections and their components have been shown to have the potential to modulate and attenuate immune responses. The objective of this study was to evaluate the potential protective effects of Clonorchis sinensis-derived protein (CSp) on ankylosing spondylitis (AS). Cytotoxicity of CSp at different doses was assessed by MTS and flow cytometry before performing experiments. Peripheral blood mononuclear cells (PBMCs) and synovial fluid mononuclear cells (SFMCs) were obtained from AS patients. Inflammat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…To the best of our knowledge, this study is the rst to demonstrate the bene cial effect of M. yokogawairelated molecules on the symptoms and cytokine imbalances in AS. Previous research showed that CSp treatment could reduce the severity of AS symptoms through the systemic and local suppression of proin ammatory mediators [12]. In this study, we aimed to nd an alternative therapeutic target for AS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To the best of our knowledge, this study is the rst to demonstrate the bene cial effect of M. yokogawairelated molecules on the symptoms and cytokine imbalances in AS. Previous research showed that CSp treatment could reduce the severity of AS symptoms through the systemic and local suppression of proin ammatory mediators [12]. In this study, we aimed to nd an alternative therapeutic target for AS.…”
Section: Discussionmentioning
confidence: 97%
“…However, using helminth products as therapeutic agents has advantages over a live infection. Lee et al previously clari ed the therapeutic effect of Clonorchis sinensis-derived protein (CSp) against AS using a murine model [12]. Any trematodes-induced proteins might be active, similar with the basis of the bene cial effect of CSp in the pathogenesis, however, it is still lacking to be known.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research indicated that C. sinensis might worsen arthritis progression, with this adverse effect potentially linked to changes in immune cell profiles and associated cytokine levels[ 17 ]. However, another study suggested that C. sinensis -induced protein could suppress new bone formation in a mouse model in vivo [ 18 ]. Notably, the role of C. sinensis infections in modulating arthritis symptoms is a multifaceted and complex phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to establish a long-standing, persistent infection model (e.g., more than 24 weeks) to track the dynamic changes of cytokines and investigate the intrinsic mechanism. Helminth infections and their components have been shown to have the potential to modulate and attenuate immune responses [25]. C. sinensis infection is carcinogenic to human [26][27][28].…”
Section: Discussionmentioning
confidence: 99%